Kontribusi Mahasiswa KUKERTA dalam Meningkatkan Kebersihan Lingkungan di Desa Teluk Beringin - Dwi Rahma Wilda; Endrisa Kurnia Putri; Fair Rizani Amalia; Hardiansyah Hardiansyah; Ilmi Yati; Jumratul Maisura; Nadira Safitri; Natasya Dewi Haya Rume; Srinurma Okta Milda (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Kukerta students at the University of Riau decided that the people in Teluk Beringin village needs to be socialized with waste management and also the provision of garbage disposal facilities there. With the concrete steps in the form of socializing and procuring of waste disposal facilities, it is intended that awareness and also the habit of disposing of waste in its place can grow in the community.